The Implementation of ESP at the Faculty of Economy and Islamic Business UIN SMH Banten - Hillalliyati, Najmi (UPT. Pengembangan Bahasa IAIN Zawiyah Cot Kala Langsa, 2022)
The needs of English at the university level are not only focused on learning general English, but also on learning specific English that relates to academic studies or professional work. English for Specific Purposes is the term given to this particular English language (ESP). As a result, the goals of this study are to investigate the current implementation of English for Specific Purposes (ESP) at UIN Sultan Maulana Hasanuddin Banten's Faculty of Economy and Islamic Business and determine whether the current implementation of ESP meets the needs of the students. This study's participants are 47 students from three different departments: Islamic Banking, Islamic Economy, and Sharia Insurance. The information was gathered using a questionnaire and an interview. The data was then qualitatively analyzed. The findings revealed that the current implementation of ESP is equally well-applied in all three departments; however, there were some issues with course materials and time allocation. Furthermore, the implementation of English class has met the needs of the students, particularly in improving their vocabulary and speaking skills. The findings suggest that lecturers should receive ESP training and that the time allocation for the ESP course be considered.